Pemeriksaan Pemenuhan Standar Getaran untuk Keselamatan dan Kenyamanan Masjid Apung Ziadatul Abror dengan Smartphone - Khoeri, Heri; Adeputra, Galuh; Sembada, Zerik (Institut Teknologi Garut, 2024)
Building structures must be in good condition and meet technical feasibility criteria. Ziadat-ul-Abror Floating Mosque on Pagatan Beach, Tanah Bumbu Regency, South Kalimantan, which was initiated and built by PT. It is hoped that Borneo Indobara will become an attraction for religious tourism in Tanah Bumbu. Apart from the security aspect, the comfort aspect for users must be a concern. Inspection of compliance with vibration standards is one of the parts that must be carried out to ensure that worshipers feel safe and comfortable when worshiping in the mosque. This is in line with what was decided in the Decree of the Minister of the Environment No. 49 of 1996 and regulated by ISO 2631-2 1989 which requires vibrations that do not damage buildings, disturb human comfort and health. From the results of the vibration test it is known that vibration in operational conditions is still within the permissible limits with a frequency between 5.66-15.86 Hz, peak vibration acceleration 0.36-1.94 %g, peak vibration velocity 0.10-1.99 mm/ det and dynamic deflection 1.22-67.37 mm.